Meninjau bahasa medis terhadap gerakan gerakan shalat: Berdiri sampai i’tidal - syauqi, gyan; nesa, sabrina; Puteri, Novita (Maliki Interdisciplinary Journal, 2025)
Prayer is an act of worship that not only has spiritual value but also holds physiological dimensions that impact human health. The activities involved in prayer, particularly the standing (qiyam), ruku’ (bowing), and i’tidal (inclination), can be studied from a medical perspective because they involve complex biomechanical mechanisms of the body. When standing, postural muscles such as the quadriceps, gluteus maximus, and erector spinae function to maintain balance and increase peripheral blood flow. The ruku’ movement provides a static stretch for the hamstrings and lower back, thus serving as flexibility training and preventing musculoskeletal pain. Meanwhile, the transition to i’tidal contributes to training neuromuscular coordination and maintaining body stability by activating core muscles. Various studies have shown that performing prayer regularly can improve posture, balance, and cardiovascular function, especially in the elderly. However, if performed without proper technique, these movements can pose risks such as back pain, increased pressure on the knee joints, or orthostatic hypotension. Therefore, understanding the medical language related to each prayer movement is crucial as an effort to integrate the values ​​of worship and health science, as well as serving as a basis for developing "healthy prayer" education to support the physical health of Muslims.